Male Meiosis as a Biomarker for Endo- to Ecodormancy Transition in Apricot - Herrera, Sara; Lora, Jorge; Fadón, Erica; Hedhly, Afif; Alonso, José Manuel; Hormaza, José I.; Rodrigo, Javier (Frontiers in Plant Science, 2022)
Dormancy is an adaptive strategy in plants to survive under unfavourable climatic conditions during winter. In temperate regions, most fruit trees need exposure to a certain period of low temperatures to overcome endodormancy. After endodormancy release, an exposure to warm temperatures is needed to flower (ecodormancy). Chilling and heat requirements are genetically determined and, therefore, are specific for each species and cultivar. The lack of sufficient winter chilling can cause failures in flowering and fruiting, compromising yield. Thus, the knowledge of the chilling and heat requirements is essential to optimize cultivar selection for different edaphoclimatic conditions. However, the lack of phenological or biological markers linked to the dormant and forcing periods makes it difficult to establish the end of endodormancy. This has led to indirect estimates that are usually not valid in different agroclimatic conditions. The increasing number of milder winters caused by climate change and the continuous release of new cultivars emphasize the necessity of a proper biological marker linked to the endo- to ecodormancy transition for an accurate estimation of the agroclimatic requirements. In this work, male meiosis is evaluated as a biomarker to determine endodormancy release and to estimate both chilling and heat requirements in apricot. For this purpose, pollen development was characterized histochemically in 20 cultivars over eight years, and the developmental stages were related to dormancy. Results were compared to three approaches that indirectly estimate the breaking of dormancy: an experimental methodology by evaluating bud growth in shoots collected periodically throughout the winter months and transferred to forcing chambers over three years, and two statistical approaches that relate seasonal temperatures and blooming dates in a series of 11-20 years by correlation and Partial Least Square regression (PLS regression). The results disclose male meiosis as a possible biomarker to determine the end of endodormancy and to estimate agroclimatic requirements in apricot.